bgbeidas wrote:

=>\((\sqrt{2}*\sqrt[3]{3})^3\)

=> \(2\sqrt{2}*3 = 6\sqrt{2}\)

C

I understand how you got 3, and how you should gt 2\sqrt{2} at the bottom.

But the 2 in the top part, when I cube it I get 8, not sure where that disappears in your process.

I think u are clear with this part =>\((\sqrt{2}*\sqrt[3]{3})^3\)

=>\((\sqrt{2}*\sqrt[3]{3})^3\)

=> (\(2^{1/2}\) * \(3^{1/3}\))\(^{3}\)

=> \(2^{3/2}\)* \(3^{3/3}\)

=>

\(2^1\)* \(2^{1/2}\)*

\(3^1\) { Because \(\frac{3}{2}\) = \(1 \frac{1}{2}\) and

\(\frac{3}{3}\) = 1 }=> \(2^1\)* \(2^{1/2}\)* \(3^1\)

=> 2*\(\sqrt{2}\) * 3

=>6\(\sqrt{2}\)

Hope this helps !!